Circle and Sphere Geometric Forms and Their Spatial Conditions - Kamalova Hillolakhan Solijonovna (Zien Journals, 2023)
This article discusses the use of geometric bodies taking into account their phase state and projection process, their main sources and use in writing or using projection cases.
Keywords: Geometric body; written description; positional relation; metric relation